Trigger Tool Based Detection of Adverse Drug Reactions in a Tertiary Care Teaching Hospital: A Prospective Observational Study - Gadde, Raja Sree; Dhanenkula, Divya Teja; Kammila, Sowjanya; Nelluri, Dharani; Polisetty, Manjusha; Kaniganti, Sowmya; Vadlamannati, Yamini; Challa, Siva Reddy; Anne, Lakshmi Pavani; Nalla, Krishna Sri; Dammalapati, Sravya Gethika (Indian Journal of Pharmacy Practice)
Background: The use of “triggers” to identify Adverse Drug reactions (ADRs) is a novel emerging method for measuring the overall level of harm from medications in a health care organization. Our main objective is to determine the incidence of adverse drug reactions in the hospitalized patients and to compare Global Trigger Tool (GTT) with conventional method to identify ADRs. Methodology: A Prospective observational study was conducted over a period of six months during November 2016-April 2017. Modified Global Trigger Tool was used to identify triggers. 16 triggers were used to identify ADRs. Causality assessment of ADRs was done using Naranjo scale and severity and harm categorization of ADRs were assessed using NCC MERP. Results: A total of 244 patient profiles were analyzed. The results reveal that 193 triggers were identified in 125 patients and 93 ADRs were found in 81 patients. Out of which, 64 (68.81%) ADRs were found by triggers and 29(31.18%) ADRs were found spontaneously without the presence of a trigger. There is a remarkable improvement in the identification of ADRs using trigger tool in comparison to traditional approach. Of 93 ADRs identified, 69 (74.19%) were probable and 24 (25.81%) were possible. Similarly, 65 (69.89%) were determined to be NCC-MERP harm category E and 28 (30.11%) were category F. Conclusion: The study results suggest that IHI global trigger tool could be useful to identify ADRs in hospitals twice as more efficiently when compared to traditional ADR identification methods. It is an effective method to enable clinical pharmacists to identify ADRs and management of the same.
Keywords: Adverse drug reactions (ADRs); IHI global trigger tool; NCC-MERP harm category; Causality; Prospective; Naranjo scale.